(untitled) (Fiep Bulletin - online, 2013)
The study focuses on the relationship between obstetrical practice and the current health paradigms. The objective is to provide an understanding of the obstetrical nurse´s actions within the current health care models and of the development of a new form of care in the birth process. The methodology was comprised of an integrative review of the literature. It was demonstrated that the flexnerian paradigm has had a marked influence upon obstetrical practices, thereby producing a medicalized, technical and fragmented birth care. Likewise, the biomedically oriented formation has influenced obstetrical nursing practice.. As a result of the ongoing paradigm shift in health, however, a different type of birth care based on quality and humanistic principles has been observed. The obstetrical nurse is developing a trusting, safe, and empathic relationships with the clients. It is concluded that even though the nurses that perform the birth care have a biomedical formation and that this care occurs at a critical moment of paradigmatic shift, one can envision an obstetrical care that is based on the dialogue, free of exploration, and that recovers the liberty of those involved in the process.